A Longitudinal Analysis of SARS-CoV-2 Antibody Responses Among People With HIV - Alcaide, Maria L.; Nogueira, Nicholas F.; Salazar, Ana S.; Montgomerie, Emily K.; Rodriguez, Violeta J.; Raccamarich, Patricia D.; Barreto, Irma T.; McGaugh, Angela; Sharkey, Mark E.; Mantero, Alejandro M.; Rodriguez, Allan E.; Beauchamps, Laura; et al. (Frontiers in Medicine, 2022)
Background: The concentration and duration of antibodies (Ab) to SARS-CoV-2 infection predicts the severity of the disease and clinical outcomes. Older people and those with HIV have impaired immune responses, worse outcomes after SARS-CoV-2 infection, and lower antibody responses after viral infection and vaccination. This study evaluated Ab response to SARS-CoV-2 in people with HIV (PWH) and without HIV and its association with age. Methods: A total of 23 COVID+PWH and 21 COVID+HIV- participants were followed longitudinally for 6-months post-mild COVID-19. IgG and IgM Ab responses were measured by ELISA. Time points and HIV status interaction were analyzed using Poisson generalized estimating equations and correlations were analyzed using non-parametric tests. Results: Median age in PWH was 55 yrs. with 28.6% females, while in the HIV- group was 36 yrs. with 60.9% females. Mean time from COVID-19 diagnosis to study enrollment was 16 days for PWH and 11 days for HIV-. Mean CD4 count for the PWH was 772.10 (±365.21). SARS-CoV-2 IgM and IgG were detected at all time points and Ab response levels did not differ by HIV status (p>0.05). At entry, age showed a weak direct association with IgG responses (ρ=0.44, p<0.05) in HIV- but did not show any association in PWH. Similar associations between age, and IgG, and HIV status emerged at day 14 (T1; ρ=0.50, p<0.05), 3 months (T3; ρ=0.50, p<0.05), and 6 months visit (T4; ρ=0.78, p<0.05) in the HIV- group. Conclusions: Ab responses in the 6-month post-SARS-CoV-2 infection did not differ by HIV status. Age was associated with IgG responses in HIV- group, but not among PWH. Results suggest that immune protection and vaccine responses is similar for PWH than for those without HIV infection.